Effect of level and time of silicon application on growth, yield and its uptake by rice (Oryza sativa) - SINGH, KALAYA; SINGH, RAGVENDERA; SINGH, J P; SINGH, YOGESHWAR; SINGH, K K (The Indian Journal of Agricultural Sciences, 2011)
A field experiment was conducted during rainy (kharif) seasons of 1999-2002 at the Varanasi to study the effect of silicon nutrition on growth, yield and silicon content as well as its uptake by ’Swania’ rice (O yzass utivu L.). Increasing lcvcl of Si up to 120 kglha significantly increased dry matter, flag leaf effectivity, yield attributes and yield of rice over its lowcr dose of 60 kg Si!k except test-weight that improved up to 180 kg Si/ha. Nitrogen and phosphorus contents in grain and straw significantly increased due to Si application up to 180 kg Si / ha. While significant improvement in potassium and zinc concentrations were recorded up to 120 kg Si /ha. Si application relatively reduced Fe and Mn concentrations in the crop. Significant response from silicon application up to 180 kg / ha was found towards Si contents and its uptake at different growth stages as well as at harvest. Use of full quantity of Si as basal was superior to other Si application time with respcct to growth, yield attributes, yield, nutrient uptake and benefit: cost ratio in rice.